2020
DOI: 10.1259/bjr.20200256
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two modalities of stereotactic body radiation therapy for peripheral early-stage non-small cell lung cancer: results of a prospective French study

Abstract: Objectives: This prospective, observational, non-randomized multicentric study was conducted to compare efficiency and toxicity using different modalities of stereotactic body radiation therapy (SBRT) in early-stage peripheral non-small cell lung cancer (NSCLC). Methods: From 9 April to 11 December, 106 patients were treated according to the local equipment availability for peripheral NSCLC with SBRT: 68 by linear accelerator equipped for SBRT and 38 by Cyberknife®. Multivariate analysis and propensity score a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This retrospective study describes factors associated with outcome, toxicity, and dosimetric parameters after lung SBRT, depending on the chosen delivery device. Our results revealed excellent local control rates of 96.8% and 94.8% at 2 and 3 years after SBRT, and a low rate of moderate-severe toxicity, values that are comparable with the literature(11)(12)(13). We have not obtained a signi cant difference in terms of local control rate after SBRT depending on the technique choice.Claude et al, prospectively analyzed the e ciency and toxicity of SBRT with CK compared to linear accelerator SBRT treatments for peripheral early stage NSCLC.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This retrospective study describes factors associated with outcome, toxicity, and dosimetric parameters after lung SBRT, depending on the chosen delivery device. Our results revealed excellent local control rates of 96.8% and 94.8% at 2 and 3 years after SBRT, and a low rate of moderate-severe toxicity, values that are comparable with the literature(11)(12)(13). We have not obtained a signi cant difference in terms of local control rate after SBRT depending on the technique choice.Claude et al, prospectively analyzed the e ciency and toxicity of SBRT with CK compared to linear accelerator SBRT treatments for peripheral early stage NSCLC.…”
supporting
confidence: 88%
“…Toxicity is described in Table 4. (13). Even retrospective, our study represents the rst one directly comparing the outcomes of patients receiving lung SBRT using three different modalities in the same radiotherapy department.…”
Section: Toxicitymentioning
confidence: 99%
“…No randomised prospective data comparing the clinical outcome of different tracking techniques has been published (and such trials are virtually impossible: few institutions have this choice in terms of equipment). However, Claude et al, in an observational prospective multicentric study, found no differences in terms of local control, progressionfree survival, overall survival and toxicity in two cohorts treated either with a Linac-or a Cyberknife-delivered SBRT (39).…”
Section: Trackingmentioning
confidence: 97%
“…For patients with lung cancer, HRQOL is usually measured by the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Core Questionnaire (QLQ-C30) in conjunction with the speci c module for lung cancer (QLQ-LC13) [7][8][9]. However, the EORTC QLQ-LC13 was developed 27 years ago and does not include items that adequately assess the adverse effects of newly developed treatments [10][11][12]. For example, the EORTC QLQ-LC13 does not assess skin rash, which is the most common side effect of targeted therapy.…”
Section: Introductionmentioning
confidence: 99%